(untitled) (Research, Society and Development, 2020)
This article discusses the topics digital technologies and the teaching of astronomy and aims to partially describe an experiment carried out in a federal educational institution in the interior of Minas Gerais, involving 40 students of integrated technical education and presents the results of a survey carried out in internet sites, seeking to identify the ten most cited applications for astronomy. The students participated in workshops for observing the night sky with the naked eye, with telescopes and with the aid of two mobile applications for astronomy. The workshops took place once a week, on the institution’s premises and outside of school hours. It is a qualitative study whose main data collection instrument was the participants’ reports and observation. As a result, a large number of mobile applications for astronomy were identified, there was a good acceptance of this technology by the research participants and it was proved the contribution that this type of technology can add to the teaching of astronomy.